Response function extrapolation of ²H nucleus in the region of high transfer energy - Buki, A.Yu.; Nenko, I.A. (Вопросы атомной науки и техники, 2000)
The experimental response functions of the ²H nucleus are extrapolated along the w-region by the power function for q=1.05 fm⁻¹.